Calcineurin-mediated IL-2 production by CD11chighMHCII+ myeloid cells is crucial for intestinal immune homeostasis - Mencarelli, Andrea; Khameneh, Hanif Javanmard; Fric, Jan; Vacca, Maurizio; El Daker, Sary; Janela, Baptiste; Tang, Jing Ping; Nabti, Sabrina; Balachander, Akhila; Lim, Tong Seng; Ginhoux, Florent; Ricciardi-Castagnoli, Paola; et al. (Nature communications, 2018)
The intestinal immune system can respond to invading pathogens yet maintain immune tolerance to self-antigens and microbiota. Myeloid cells are central to these processes, but the signaling pathways that underlie tolerance versus inflammation are unclear. Here we show that mice lacking Calcineurin B in CD11chighMHCII+ cells (Cnb1 CD11c mice) spontaneously develop intestinal inflammation and are susceptible to induced colitis. In these mice, colitis is associated with expansion of T helper type 1 (Th1) and Th17 cell populations and a decrease in the number of FoxP3+ regulatory T (Treg) cells, and the pathology is linked to the inability of intestinal Cnb1-deficient CD11chighMHCII+ cells to express IL-2. Deleting IL-2 in CD11chighMHCII+ cells induces spontaneous colitis resembling human inflammatory bowel disease. Our findings identify that the calcineurin-NFAT-IL-2 pathway in myeloid cells is a critical regulator of intestinal homeostasis by influencing the balance of inflammatory and regulatory responses in the mouse intestine.
Keywords: geny MHC třídy II; myši; Mice, Inbred C57BL; mužské pohlaví; kalcineurin; Male; kolitida; Intestines; buňky Th17; Female; Humans; Genes, MHC Class II; lidé; Th1 Cells; Interleukin-2; ženské pohlaví; Homeostasis; myši inbrední C57BL; Calcineurin; Animals; interleukin-2; střeva; zvířata; Mice; Th17 Cells; CD11c Antigen; Mice, Knockout; myeloidní buňky; Myeloid Cells; Th1 buňky; homeostáza; Colitis; antigeny CD11c; myši knockoutované